Pengembangan Kambing Kacang Berbasis Pakan Limbah Ampas Sagu (Metroxylon Sago) - Rosalia Paulina Nogo; Rahim Darma; Syatrianty A. Syaiful (AGRICOLA, 2019)
This study aims to increase the weight gain of peanut goat and the effect of the use of sago pulp waste fermentation on consumption (efficiency), palatability of feed ingredients provided and digestibility of dry matter. Quantitative research methods using a randomized block design (RAK), and analysis of variance and t-tests were performed. The results showed that body weight gain of 20% goat beans and 30% sago pulp fermentation in male goats had a significant effect on body weight gain, obtained 20%= 7.05 kg and 30% = 12.3 kg. Female goats control body weight better at 6.7 kg followed by 30% sago pulp fermentation treatment of 5.7 kg and 20% = 4.48 kg. The significant difference in 30% of male and female goats (P <0.05) ie 12.3kg and 5.7 kg. Consumption of bean goat feed at 30% treatment, 23,680gr grass + sago pulp.250gr better than control, 22.370gr grass. The treatment resulted in a body weight effect on feed efficiency between 7.25% -13.31%. Goat male beans increased the digestibility of dry matter in the treatment of 30% significantly different, namely 63.25%. Female goats did not show a significant difference of 30% (59.40%). The addition of 30% sago can increase bodyweight, so can be used as substitution food in the dry season.